Analisis Volatilitas Harga Beras dan Segmentasi Wilayah Berbasis Data Digital - Firmansyah, Achmad Fauzi Bagus; Sari, Dwi Puspita (Politeknik Statistika STIS, 2025)
Rice is a strategic food commodity whose price movements directly impact the economy and public welfare, particularly the SPHP (Stabilization of Food Supply and Prices) rice distributed by Perum Bulog. To maintain food security, data recentness is crucial to understand rice price fluctuation patterns and volatility characteristics across areas. This study uses data obtained through web crawling from the digital platform of the National Food Price Panel (PHPN) as a novel digital data source. The analysis results indicate that, in general, SPHP rice prices do not fluctuate significantly, but they remain sensitive to specific events, showing temporary volatility that tends to stabilize over time. The segmentation results reveal three regional clusters with distinct volatility characteristics. The findings of this study are expected to serve as a foundation for formulating more effective and accurately targeted food policies.